Physiological and transcriptomic analysis of purple flowering stalks (Brassica campestris var. purpurea) under cadmium stress and exogenous glutathione application - Huang, Zhi (Plant physiology and biochemistry : PPB, 2024)
Copyright © 2024 Elsevier Masson SAS. All rights reserved.